META-ANALISIS VARIASI PENELITIAN DARI PENELITI AKUNTANSI DI INDONESIA - Tycho Brahe Hutagalung; Dwi Cayo Utomo (Diponegoro Journal of Accounting, 2017)
The importance of a research is motivated by several objectives. First, with the research we can improve our knowledge that has not been known before. Second, a research can also be a material of performance evaluation. The purpose of this study is to determine the mapping and trends of research conducted by researchers in Indonesia.            In attempt to reach research goals this thesis use data analysis method in form of qualitative analysis which is an analysis based on logical opinion presented in form of words and written understanding matching the acquired data. Thus can be obtained a clear view of the mapping and trends of accounting research in Indonesia.            This study uses secondary data from Proceedings National Symposium Accounting (SNA) starting from 2012-2014. The analytical technique used in this study is qualitative explanatory. The reason of the use of this technique is to design a decent description about the research project, and to present the data systematically and objective. From this analysis can be concluded that the results of accounting research in Indonesia is quite diverse but for some categories there are significant differences in terms of quantity.